Comparing the applicability of temporal gait symmetry, variability and laterality in bilateral gait conditions: A feasibility study of healthy individuals and people with diabetic neuropathy. (January 2022) - Tan, Adin Ming; Weizman, Yehuda; Van Netten, Jaap J.; Fuss, Franz Konstantin
Abstract: Background: Gait symmetry is used to measure pathological gait but is usually applied to unilateral pathology. This study aims to investigate bilateral impairment using existing and new gait symmetry methods. Methods: 15 healthy volunteers and 14 people with diabetes and distal symmetrical polyneuropathy participated in this study. Three temporal parameters (combined step, stance phase and double stance), expressed as a percentage, were extracted for comparing gait symmetry between healthy volunteers and patients using in-shoe measurements (Pedar-X). Three indices were calculated, including the widely used Symmetry Index; the well-established Variability Index; and the newly developed Laterality Index, that calculates how well distributed a condition is across both legs. Findings: In all three parameters, Symmetry and Variability Index proved to be significantly greater in the diabetic cohort ( p -values range < 0.001–0.0226). The Laterality Index was significantly greater in the diabetic cohort for the stance and double stance phases ( p -values 0.03 and < 0.001), but not for the combined step ( p -value 0.3953). In both cohorts, Laterality Index <1 (fractional laterality) was associated with small Symmetry Index data, whereas in large Symmetry Index data, the Laterality Index was 1 (unilateral condition). Interpretations: Gait symmetry and variability are useful tools for quantifying locomotion and the effects of aging and diseases. We have shown the ability of these two indices in differentiating two extreme groups of individuals. For cases with small Symmetry Index, the current method of using an arbitrary value is not ideal. The newly developed Laterality Index can be used to decide on the cut-off between symmetrical and asymmetrical gait. Highlights: Gait Symmetry measurement for use in bilateral gait disorders. Gait Symmetry Index is insufficient in quantifying degree of gait disorder. New index for measurement of gait laterality. Use of new index to decide cut-off between symmetrical and asymmetrical gait. Correlation of indices to healthy and diabetic participants.